Meningkatkan Kepuasan Pasien melalui Optimalisasi Kualitas Pelayanan, Fasilitas Kesehatan, dan Citra Puskesmas Sebangki, Kalimantan Barat - Theodora Dona Mila; Farida Yuliaty; Rukhiyat Syahidin; Taufan Nugroho; Kosasih Kosasih (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the influence of healthcare service quality, healthcare facilities, and community health center (Puskesmas) image on outpatient satisfaction at Sebangki Community Health Center, Landak Regency, West Kalimantan. The research employed a quantitative approach with data collected through questionnaires distributed to 128 outpatient respondents. Data analysis was conducted using validity and reliability tests, multiple linear regression, correlation coefficient, and coefficient of determination. The results indicate that service quality, healthcare facilities, and Puskesmas image have a positive effect on patient satisfaction, both partially and simultaneously. The findings affirm that patient satisfaction can be enhanced through improvements in service quality, the availability and comfort of facilities, and the strengthening of a positive institutional image in the community. Among the three variables, healthcare service quality showed the lowest average value, suggesting the need for greater attention in continuous improvement efforts. The implications of this study may serve as valuable input for Puskesmas management in formulating more effective service strategies to improve patient satisfaction and loyalty.